Just as I thought - Paley, Grace 1922-2007 (Farrar, Straus, Giroux, 1998)
Just As I Thought is as close to an autobiography as anything we are likely to have from this quintessentially American writer. In it we get a chance to see Grace Paley not only as a writer and "troublemaker" but also as a daughter, sister, mother, and grandmother. Through her descriptions of her childhood in the Bronx and her experiences as an antiwar activist to her lectures on writing and her recollections of other writers, these pieces are always alive with Paley's inimitable voice, humor, and wisdom.
Keywords: Paley, Grace; Paley, Grace -- 1922-2007; Geschichte 1900-2000; Authors, American -- 20th century -- Biography; Autobiografie; Biografie